Institutionalizing Sustainable Finance and Carbon Markets: Evidence from an Emerging Economy Stock Exchange - Dwi Nova Wijaya; Rommy Mochamad Ramdhani; Dewi Fitrotus Sa'diyah (Owner : Riset dan Jurnal Akuntansi, 2026)
This study examines the role of the Indonesia Stock Exchange (IDX) as an institutional driver of sustainable finance and carbon market development in an emerging economy context. Drawing on longitudinal sustainability report data spanning 2018 to 2024, the study applies institutional theory and qualitative longitudinal content analysis to trace IDX's transformation from a reactive, compliance-oriented organization under POJK No. 51/2017 into a proactive ecosystem builder advancing Environmental, Social, and Governance (ESG) infrastructure across Indonesian capital markets. The findings reveal a progressive institutionalization trajectory unfolding across three distinct phases: regulatory compliance (2018–2019), ecosystem construction (2020–2022), and innovation leadership (2023–2024). Over this period, IDX launched multiple ESG indices including the ESG Leaders Index (ESGL), integrated the Sustainalytics ESG Risk Rating, joined the United Nations Sustainable Stock Exchanges (UN SSE) initiative, established the Bursa Karbon Indonesia as Southeast Asia's first regulated carbon exchange, and introduced the IDX Net Zero Incubator. Quantitative performance data document growing ESG product adoption, with net asset value reaching IDR 7.18 trillion in 2024, alongside early carbon market growth reflected in 100 registered participants and 420,987 tonnes of CO?eq retired. Nevertheless, structural barriers persist, including limited market participant awareness, carbon price discovery challenges, and insufficient ESG data comparability across market actors. Theoretically, this article contributes to the nascent literature on Self-Regulatory Organizations (SROs) as active agents of sustainable finance institutionalization, while extending the application of institutional theory to capital market contexts in developing economies.